Ultrasound-guided minimally invasive thoracotomy for removal of migrating grass Awn in a Cat - Vicente Francisco Ratto Valderrama; Federica Valeri; Domenico Caivano; Giulia Moretti; Antonello Bufalari (Veterinary Research Communications, 2026)
Migrating grass awns are a rare cause of thoracic reactions in cats, resulting in pleural effusion, inflammation, infection and granulomatous responses. Diagnosis and localization are challenging, and treatment commonly requires invasive surgical intervention. We report a case of a 5-year-old, neutered male, domestic shorthair cat referred for pleural effusion and suspected intrathoracic vegetal foreign body. Thoracic ultrasonography confirmed the presence of pleural effusion and a linear hyperechoic structure within the pleural space was visualized. An ultrasound-guided minimally invasive thoracotomy was performed through the right fifth intercostal space and intraoperative ultrasonography was useful to precisely locate and remove the foreign body using a Hartmann ear forceps. Cytological analysis was performed on the pleural fluid and bacteriological analysis was performed on both the pleural fluid and the retrieved foreign body. The cytologic findings were consistent with an exudative effusion but no bacteria were isolated on both direct and enrichment bacterial cultures; empirical antibiotic treatment with marbofloxacin was continued. The patient recovered uneventfully, and follow-up revealed complete resolution of the clinical signs. This case report highlights the effectiveness of ultrasound-guided minimally invasive approach for intrathoracic vegetal foreign body removal in a cat. The transthoracic and intraoperative ultrasound can be useful for visualization and exact localization of the grass awn, minimizing surgical trauma and improving the outcome.

Hypercalcemia of malignancy in a dog with cutaneous apocrine gland carcinoma and malignant myoepithelioma - Ludovica Emiliani Pescetelli; Ambra Luisa Misia; Giulia Moretti; Giovanni Angeli; Maria Teresa Antognoni; Antonello Bufalari; Eleonora Scorsi; Elvio Lepri (Veterinary Research Communications, 2026)
Humoral Hypercalcemia of Malignancy (HHM) is a commonly reported condition in dogs affected by several cancers, mostly T-cell lymphoma and anal sac gland carcinomas, but also other type of tumors. We report the case of a 6-years-old, female neutered Border Collie with an ulcered nodule on the right retromandibular region, that had mild serum total calcium elevation (14,1 mg/dl; reference range (RR): 8,4 to 11 mg/dl) in the absence of clinicopathological abnormalities or imaging finding suggesting any known cause of hypercalcemia. Histologically, the tumor had a tubular epithelial component, admixed with a second, dominant, myoepithelial one; immunohistochemically, the former strongly reacted with anti-Cytokeratin antibodies, while the latter had a weak and patchy immunoreactivity both to Cytokeratin and a-SMA, while Vimentin and Calponin immunostaining was strong and diffuse, suggesting the diagnosis of apocrine gland carcinoma and malignant myoepithelioma. After the excision of the tumor, calcium decreased within limits (8.8 mg/dl RR: 8.4 to 11. mg/dl). In the author’s knowledge, this is the first report of HHM associated with apocrine sweat gland carcinoma in the dog.

Food Safety and quality of some Italian honey: Study of long-persistent contaminants (heavy metals and PFAS) in different production areas in southern Italy - Sergio Passarella; Simone Moretti; Alessia Iannone; Fabiana Carriera; Sonia Ganassi; Dalila Di Criscio; Loretta De Giorgi; Giulia Corazzi; Ivan Notardonato; Carolina Barola; Roberta Galarini; Pasquale Avino; et al. (Food Chemistry, 2026)

The zero-burden Illusion: Rethinking allocation methods for secondary raw materials in LCA - Giulia Del Serrone; Gennaro Riccio; Laura Moretti (Resources, Conservation and Recycling, 2025)

MRI-guided stereotactic radiotherapy for oligometastatic peritoneal carcinomatosis: toward integrative oncologic approaches - Angela Romano; Giuditta Chiloiro; Luca Boldrini; Giulia Panza; Ilaria Castanò; Maura Campitelli; Isabella Costamagna; Irene Moretti; Matteo Nardini; Marco Valerio Antonelli; Claudio Votta; Lorenzo Placidi; et al. (Clinical & Experimental Metastasis, 2025)

Effect of simulated prolonged heat wave on biometric performance and HSP70 synthesis in the striped venus clam Chamelea gallina - Antonina De Marco; Vito Antonio Baldassarro; Maura Cescatti; Marzia Moretti; Laura Calzà; Luciana Giardino; Francesco Dondi; Maria Giulia Ferrari; Pier Paolo Gatta; Luca Parma; Alessio Bonaldo (Aquaculture, 2025)

Cradle-to-cradle life cycle assessment of railway prestressed concrete sleepers: A state-of-the-art review and strategies for reducing environmental impacts - Giulia Del Serrone; Gennaro Riccio; Laura Moretti (Resources, Conservation and Recycling, 2025)

Evaluation of attenuated Salmonella Typhimurium (STMΔznuABC) anticancer activity on canine mammary cancer-associated fibroblasts - Barbara Chirullo; Floriana Fruscione; Genny Del Zotto; Filippo Dell'Anno; Michela Tarantino; Ilaria Porcellato; Paola Petrucci; Chiara Grazia De Ciucis; Antonello Bufalari; Lisa Guardone; Katia Cappelli; Giulia Moretti; et al. (Research in Veterinary Science, 2024)

Anthropogenic litter in a Mediterranean coastal wetland: A heterogeneous spatial pattern of historical deposition - Corrado Battisti; Giulia Cesarini; Luca Gallitelli; Filippo Moretti; Massimiliano Scalici (Marine Pollution Bulletin, 2024)

Assessing failure of transfer of passive immunity by gamma-glutamyl-transferase activity and serum refractometry in holstein-friesian calves affected by neonatal diarrhea - Giulia Sala; Valerio Bronzo; Antonio Boccardo; Alessia Libera Gazzonis; Pierangelo Moretti; Vincenzo Ferrulli; Angelo Giovanni Belloli; Laura Filippone Pavesi; Gaia Pesenti Rossi; Davide Pravettoni (Veterinary Research Communications, 2023)
Hardly published data are available to diagnose the failure of transfer of passive immunity (FTPI) in calves affected by neonatal calf diarrhea (NCD). This study evaluated the diagnostic performance and differences among optical serum total protein (STP) concentration and gamma-glutamyl-transferase (GGT) activity for assessing FTPI in diarrheic Holstein Friesian calves. 72 diarrheic and 19 healthy Holstein Friesian calves aged 1 to 10 days were enrolled. Each calf underwent a complete clinical examination and dehydration assessment. The effect of dehydration status and age on the correlation between the two methods under study (STP and GGT) and the gold standard (Immunoglobulin G [IgG] measured with RID) was investigated with Spearman’s correlation index R for ranks. Serum total protein concentration and GGT activity were analyzed by receiver operating characteristic (ROC) curve analysis to identify the optimal cut-off point to distinguish between diarrheic calves with or without FTPI, also considering the effects of dehydration and age. The results show that GGT activity was affected by the age of calves, while STP was influenced by dehydration. The cut-offs to distinguish calves with IgG < 10 g/L were < 52 g/L of STP in normohydrated calves, < 58 g/L of STP in dehydrated calves, and < 124 IU/L of GGT in calves with aged between 3 and 10 days. In nondehydrated diarrheic calves, the STP refractometer showed better diagnostic accuracy. In dehydrated calves aged between 3 and 10 days, however, its accuracy drops, and it is advisable to use GGT activity.

A stepwise regression to identify relevant variables affecting the environmental impacts of clinker production - Giulia Del Serrone; Laura Moretti (Journal of Cleaner Production, 2023)

Emission estimates and air quality simulation on Lombardy during lockdown - Alessandro Marongiu; Elisabetta Angelino; Giulia Malvestiti; Marco Moretti; Giuseppe Fossati; Edoardo Peroni (Air Quality, Atmosphere & Health, 2023)

Ultrastructural study of spermatogenesis in KSR2 deficient mice - Elena Moretti; Giulia Collodel; Lucia Mazzi; Ilaria Russo; Emanuele Giurisato (Transgenic Research, 2015)

Evaluation of viral load in infants hospitalized with bronchiolitis caused by respiratory syncytial virus - Carolina Scagnolari; Fabio Midulla; Carla Selvaggi; Katia Monteleone; Enea Bonci; Paola Papoff; Giulia Cangiano; Paola Di Marco; Corrado Moretti; Alessandra Pierangeli; Guido Antonelli (Medical Microbiology and Immunology, 2012)